Optimization of Remazol Black B Removal Using Biochar Produced from Caulerpa scalpelliformis Using Response Surface Methodology - R. Gokulan; S. Balaji; P. Sivaprakasam (Advances in Materials Science and Engineering)
Optimization of process conditions for the removal of Remazol Black B was investigated using response surface methodology (Box–Behnken design). The biodecolorization of dye was studied using biochar produced from waste biomass of Caulerpa scalpelliformis (marine seaweeds). The reactions were optimized by varying sorbent dosage, solution pH, temperature, and initial dye concentration. The results indicated that dye removal efficiency of 80.30% was attained at an operating condition of 4 g/L (sorbent dosage), 2.0 (solution pH), 35°C (temperature), and 0.25 mmol/L (initial dye concentration). The regression coefficient of the developed model was calculated to be 97% which shows good fit of the model.